BS ISO 16796. Nuclear energy. Determination of Gd2O3 content in gadolinium fuel blends and gadolinium fuel pellets by atomic emission spectrometry using an inductively coupled plasma source (ICP-AES). (1st December 2020) - British Standards Institution,
No abstract available